Hybridization and introgression events in cooccurring populations of closely related grasses (Poaceae: Stipa) in high mountain steppes of Central Asia. - Patar Sinaga; Ewelina Klichowska; Arkadiusz Nowak; Marcin Nobis (PLoS ONE, 2024)
Stipa is a genus comprising ca. 150 species found in warm temperate regions of the Old World and around 30% of its representatives are of hybrid origin. In this study, using integrative taxonomy approach, we tested the hypothesis that hybridization and introgression are the explanations of the morphological intermediacy in species belonging to Stipa sect. Smirnovia, one of the species-rich sections in the mountains of Central Asia. Two novel nothospecies, S. magnifica × S. caucasica subsp. nikolai and S. lingua × S. caucasica subsp. nikolai, were identified based on a combination of morphological characters and SNPs markers. SNPs marker revealed that all S. lingua × S. caucasica samples were F1 hybrids, whereas most of S. magnifica × S. caucasica samples were backcross hybrids. Furthermore, the above mentioned hybrids exhibit transgressive morphological characters to each of their parental species. These findings have implications for understanding the process of hybridization in the genus Stipa, particularly in the sect. Smirnovia. As a taxonomic conclusion, we describe the two new nothospecies S. × muksuensis (from Tajikistan) and S. × ochyrae (from Kyrgyzstan) and present an identification key to species morphologically similar to the taxa mentioned above.